Cholecystitis, cholelithiasis, and ganglioneuromatosis of the gall bladder: an unusual presentation of MEN type 2b. Issue 11 (November 1993) - Chetty, R; Clark, S P
Abstract : A 40 year old man with multiple endocrine neoplasia type 2b (MEN 2b) presented with cholecystitis caused by gall stones. Twenty four years earlier, he had had a partial thyroidectomy for a cold nodule. At his initial presentation MEN 2b with medullary carcinoma of the thyroid had not been made. This was diagnosed while investigating his gall bladder symptoms and he was found to have asymptomatic residual medullary thyroid carcinoma and bilateral adrenal phaeochromocytomas. The cholecystectomy specimen contained several mixed calculi and extensive ganglioneuromatosis with large, prominent nerves containing ganglion cells in the gall bladder wall.